Mustard plant ash: a source of micronutrient and an adsorbent for removal of 2,4-dichlorophenoxyacetic acid - Trivedi, Nikhilesh S.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2016)
The work highlights the utilization of an agricultural waste mustard plant ash (MPA) as a soil additive and an adsorbent. MPA was characterized by X-ray fluorescence (XRF), energy-dispersive X-ray spectroscopy (EDX), proximate analysis, CHNS analysis, Brunauer-Emmett-Teller (BET) surface area analysis, zeta potential measurements, Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). XRF analysis confirmed the presence of CaO (31.35 %), K2O (18.55 %), and P2O5 (6.99 %), all of which act as micronutrients to plants. EDX also confirms high amount of elemental O, Ca, K, and P. The adsorptive ability of MPA was investigated using a commonly used herbicide, 2,4-dichlorophenoxyacetic acid (2,4-D), as a representative chemical. Batch adsorption experiments were conducted to study the effect of different operational parameters such as adsorbent dose, initial 2,4-D concentration, contact time, and temperature on the adsorption process. Data from experiments were fitted to various kinetic and isothermal models. The pseudo-second-order kinetic model was found to show the best fit (R (2) > 0.99), with the highest k (2) value of the order 10(5). Based on the study results, dosage of MPA/hectare for different crops has been recommended for effective removal of 2,4-D. To our knowledge, this is the first study in which MPA has been characterized in detail and investigated for dual applications (as an adsorbent and as a soil additive).

Methodology of evaluating sustainability index of a biomass processing enterprise: a case study of native cow dung-urine biorefinery - Joglekar, Saurabh N.; Darwai, Vivek; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Environmental Science and Pollution Research, 2019)
Agriculture and its allied sector contribute significantly to the gross domestic product of every country. Several small-scale enterprises engaged in waste biomass processing have been setup recently. Such industrial setups not only help in solving the waste management issues but also play an important role in offering employment at the grass root level generating a significant social impact along with economic advantage to the local entrepreneur. Hence, assessment of such biomass processing enterprise (BPE) based on economic, environment, and social parameters has become necessary. In this paper, a general framework for sustainability assessment is discussed using a case study of cow dung-urine biorefinery as a representative BPE. Real-time data of BPE has been collected for evaluation and a sustainability index (SI) is evaluated using multicriteria decision method. The SI is calculated as per the weightage assigned and value function of the indicator and criteria. The SI for the BPE was observed to be 0.69 for the chosen set of criteria and indicator and weightages. A sensitivity analysis has been performed to check the dependence of the results on the weightages assigned to various criteria and indicators. It was also observed that the results were more sensitive to the indicators having a low value function.
Keywords: Indicator analysis; MIVES; Multicriteria decision analysis; Performance evaluation; Sustainability assessment framework